2005
DOI: 10.1007/s10578-004-3490-9
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Length of Stay in Child Residential Treatment

Abstract: A sample of 126 consecutively admitted residential treatment children (mean age = 9.86, SD=1.84; 70.6% male; 42.1% African American; 50% Caucasian) were studied over a five-year period to identify predictors of length-of-stay. Cox regression was the primary statistical method used to analyze psychiatric and behavioral rating data for children assessed by teachers and treatment staff using the Devereux Scales of Mental Disorders (DSMD). Parental alcohol abuse, and children's age, medication status, race, initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…These results support previous research that found a plateau of positive effects of longer time in treatment on youth outcomes (Green et al 2001;Hussey and Guo 2005;Zimmerman et al 2000). The most drastic changes happens between 1 and 6 months (approximately between 30 and 183 days, Group 1 above) of treatment where there is a strong positive predictive relationship between a longer time in treatment and a greater improvement in overall functioning, in several life domains (School/Work, Home, Behavior towards Others, Moods/Emotions), and in restrictiveness of living environment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results support previous research that found a plateau of positive effects of longer time in treatment on youth outcomes (Green et al 2001;Hussey and Guo 2005;Zimmerman et al 2000). The most drastic changes happens between 1 and 6 months (approximately between 30 and 183 days, Group 1 above) of treatment where there is a strong positive predictive relationship between a longer time in treatment and a greater improvement in overall functioning, in several life domains (School/Work, Home, Behavior towards Others, Moods/Emotions), and in restrictiveness of living environment.…”
Section: Discussionsupporting
confidence: 91%
“…Researchers also found plateaus in improvement occurring at varying time points throughout treatment. For example, Zimmerman et al (2000) found plateaus occurring between 3 and 6 months following admission to treatment, while other sources found plateaus occurring between 30 and 90 days of residential treatment (Hussey and Guo 2005), or after only 30 days of treatment (Green et al 2001). Due to inconsistencies in previous literature, use of relatively small sample sizes (ranging from 27 to 225 youth), and limited range of youth's functioning previously assessed; there is a need to identify these effects with larger samples of youth, across multiple sites, and throughout the many domains in the youth's life in order to examine trends in youth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The available literature suggests, however, that there can be differential change trajectories relative to the degree of presenting symptoms, specific client/family characteristics, and treatment program or agency. Hussey and Guo [10] noted that the children with the highest critical pathology at admission had the slowest rate of change measured at discharge. Conversely, the group with the lowest critical pathology at the first time point had the fastest rate of discharge.…”
mentioning
confidence: 99%
“…There remains a lack of research about the specific characteristics of children and their experiences within RTCs (Brady & Caraway, 2002;Hussey & Guo, 2005;Jones & Lansdverk, 2006;Moses, 2000;Nickerson et al, 2011). According to Peacock and Daniels (2006), most children in RTCs have directly or indirectly experienced persistent relational trauma.…”
Section: Characteristics Of Children and Adolescents With Trauma Histmentioning
confidence: 99%
“…As a result, a priority for administrators, funding sources, and mental health professionals is to better understand how to most effectively treat the individuals who are placed in this setting. Nevertheless, very little em-pirical data have been collected to provide this understanding (Brady & Caraway, 2002;Greenwald et al, 2012;Hussey & Guo, 2005;Jones & Lansdverk, 2006).…”
Section: Characteristics Of Children and Adolescents With Trauma Histmentioning
confidence: 99%